Vertucci's root canal configuration of 11,376 mandibular anteriors and its relationship with distolingual roots in mandibular first molars in a Cantonese population: a cone-beam computed tomography study - Yeqing Yang; Chong Jiang; Ming Chen; Junkai Zeng; Buling Wu (BMC, 2022)
Abstract Background Cone-beam computed tomography (CBCT) was used to study the root canal system of mandibular anteriors (MAs) in a Cantonese population and to evaluate the correlation between the complicated root canal configurations of mandibular lateral incisors (MLIs) and the presence of distolingual roots (DLRs) in mandibular first molars (MFMs). Methods A total of 11,376 mandibular anterior teeth were scanned by CBCT. Those whose images met the inclusion criteria were first analysed according to Vertucci's root canal configuration and then grouped based on gender, age, and side, and their effects on root canal morphology were analysed. Finally, statistical analysis was used to evaluate the correlation between the complicated root canal configurations of MLIs and the existence of DLRs in MFMs. All statistical analyses were performed by using SPSS 25.0 software. Quantitative data are presented as the mean ± standard deviation. Student's t tests were used to calculate statistical significance. P < 0.05 was considered statistically significant. Results In MAs in the Cantonese population, all mandibular central incisors (MCIs) and MLIs had one root, and 0.37% of mandibular canines (MCs) had two roots. The most common Vertucci's root canal configuration was Vertucci I followed by Vertucci III. A total of 30.91% of MLIs and approximately 8% of MCIs and MCs have complicated root canal configurations. There were no significant differences in the prevalence of DLRs in MFMs and the incidence of complicated root canal configurations of MLIs between males and females or between the right and left teeth. However, a significant difference was found in different age groups of root canal configurations in MLIs. Moreover, significant ipsilateral and contralateral correlations between MFMs with DLRs and MLIs with complicated root canal configurations were observed on both sides. Conclusion In Cantonese population, the possibility of complicated root canal configuration in MLIs was higher, when DLR appeared in MFMs.